Rancang Bangun dan Analisis Screen Cutting Machine Guna Meningkatkan Produktivitas Pemotongan - Timotius Anggit Kristiawan; Alfiando Satrio Wibowo; Arif Hidayat (Journal of Mechanical Engineering and Applied Technology, 2023)
The material cutting process can be done with a variety of mechanical power options that can be used, ranging from manual cutting methods that require manual skills, to semi-automatic and automatic cutting that utilize advanced technology to increase efficiency and accuracy. The process of cutting materials at PT Suri Tani Pemuka is still done manually, by relying on the skills of the workers' hands. The impact resulting from the manual cutting process is that the cutting results are not according to the standard size determined by the company, so that there are still many NG products found from the cutting process. Based on these problems, it is necessary to have a solution, namely by designing a screen cutting machine to increase cutting productivity. The methods used in this research include Identification of need, Definition of problem, Synthesis, Analysis and Optimization, Evaluation, and Presentation. The test was carried out to test the quality of the screen cut results. The results obtained from this study are screen cutting machines for cutting screen equipment with an increase in the percentage of successful screen cutting by 33.3% from 50% to 83.3%.